Peusijuek Local Wisdom Resilience of the Acehnese Within the Cultural Globalization Discourse - Adi Kasman; M. Ikhwan; Roni Hidayat (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2022)
This research is an effort to explain the experiences of acehnese people in defending local culture from the rapid flow of cultural globalization. Cultural globalization is the dissemination of ideas, meanings, and values that transcend cultural boundaries because they are assisted by the internet, media, and foreign travel so that it becomes a challenge for the local wisdom of the community. The purpose of this study is to see the transformation process carried out by the Acehnese people in maintaining the local wisdom of peusijuek as a cultural heritage of the Acehnese people in the past. The method used in this study is qualitative research with an anthropological approach to identify indicators used by the Acehnese people in maintaining the existence of local wisdom. This research was carried out in Aceh Barat Regency by considering the locus that was very supportive to be observed by the author. The results of the study show that the transformation process of peusijeuk local wisdom involves various dimensions such as educational institutions, traditional institutions, and also the level of public awareness of the importance of the value of local wisdom.